Determinants of meconium aspiration syndrome among neonates admitted to neonatal intensive care unit at Nigist Eleni Mohammed Memorial Comprehensive Specialized Hospital, South Ethiopia: Unmatched case–control study - Seifu Awgchew; Elias Ezo (SAGE Open Medicine)
Objective: To identify determinants of meconium aspiration syndrome among neonates admitted to the neonatal intensive care unit at Nigist Eleni Mohammed Memorial Comprehensive Specialized Hospital, South Ethiopia, in 2022. Method: A facility-based unmatched case–control study was used to identify meconium aspiration syndrome with a total sample size of 249 from January to April 2022. Data were entered by using EpiData version 3.1 and analyzed using SPSS version 24 software. Descriptive findings were presented by frequency tables and percentages. Multicollinearity was checked and the goodness of fit test was done. To determine the independent determinants associated with meconium aspiration syndrome, bivariate analysis was done and variables with a p value of <0.05 were taken to multivariate logistic regression analysis. Adjusted odds ratio with a 95% confidence interval was calculated, and statistical significance was declared at a p value less than 0.05. Result: Two hundred forty-nine (83 cases and 166 controls) mothers with their respective neonates were included in this study and that made the overall response rate 100%. Preeclampsia (adjusted odds ratio: 3.35, 95% confidence interval: 1.02, 10.97), antepartum hemorrhage (adjusted odds ratio: 3.63, 95% confidence interval: 1.50, 8.78), duration of labor (adjusted odds ratio: 4.34, 95% confidence interval: 1.83, 10.30), premature rupture of membrane (adjusted odds ratio: 16.02, 95% confidence interval: 5.66, 45.29), and obstructed labor (adjusted odds ratio: 4.57, 95% confidence interval: 1.42, 14.70) were determinants of meconium aspiration syndrome. Conclusion: In this study, preeclampsia, antepartum hemorrhage, duration of labor, premature rupture of membrane, and obstructed labor were determinants of meconium aspiration syndrome. Therefore, to reduce the risk of meconium aspiration syndrome, prevention, early identification, and management of these obstetrical factors may help to reduce meconium aspiration syndrome locally.